2011
DOI: 10.3945/an.110.000174
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Neurogenesis: Making New Neurons from Development to Adulthood

Abstract: Stem cell proliferation, neuronal differentiation, cell survival, and migration in the central nervous system are all important steps in the normal process of neurogenesis. These mechanisms are highly active during gestational and early neonatal brain development. Additionally, in select regions of the brain, stem cells give rise to new neurons throughout the human lifespan. Recent work has revealed key roles for the essential trace element zinc in the control of both developmental and adult neurogenesis. Give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(73 citation statements)
references
References 35 publications
2
65
0
3
Order By: Relevance
“…In comparison to previous studies in adult brain, we found higher levels of zinc in cerebral organoids, although compatible in scale of dosage (Table 2). While higher concentrations of zinc in adult brain are toxic to neural cells and also cause axonal degeneration in mice (47), zinc modulates the proliferation of stem cells and neuronal differentiation during neurogenesis (31)(32)(33). In accordance, previous data from our group have demonstrated increased zinc during neural differentiation of human pluripotent stem cells (48), which may highlight the importance of zinc for the commitment of neural stem cells and justify why levels found in cerebral organoids are subtly higher than those described in the adult brain (Table 2) (9,49,50).…”
Section: Implications Of Trace Elements Detected In Cerebral Organoidmentioning
confidence: 99%
“…In comparison to previous studies in adult brain, we found higher levels of zinc in cerebral organoids, although compatible in scale of dosage (Table 2). While higher concentrations of zinc in adult brain are toxic to neural cells and also cause axonal degeneration in mice (47), zinc modulates the proliferation of stem cells and neuronal differentiation during neurogenesis (31)(32)(33). In accordance, previous data from our group have demonstrated increased zinc during neural differentiation of human pluripotent stem cells (48), which may highlight the importance of zinc for the commitment of neural stem cells and justify why levels found in cerebral organoids are subtly higher than those described in the adult brain (Table 2) (9,49,50).…”
Section: Implications Of Trace Elements Detected In Cerebral Organoidmentioning
confidence: 99%
“…All very-low-birth-weight (VLBW) 4 neonates (birth weight: 401-1500 g or a gestational age of 24 to 32 wk), consecutively observed in a neonatal intensive care unit, were considered eligible for the study. Exclusion criteria were as follows: congenital or maternal infections, immunodeficiency, malformations, syndromes, genetic defects, evidence of infection, and necrotizing enterocolitis (NEC) diagnosed before enrollment, critically ill conditions (defined as a blood pH ,6.8 or hypoxia with persistent bradycardia for $1 h), and hospitalization for ,1 wk.…”
Section: Participantsmentioning
confidence: 99%
“…It is required for the production of a wide variety of enzymes involved in essential metabolic patterns (ie, protein synthesis, nucleic acid metabolism, immune function, and organogenesis) (1)(2)(3). Zinc is crucial for the development of the brain, respiratory and intestinal tracts in pre-and postnatal life (1,(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…However, more than 30% of the world's population is Zn deficient, including around 10% of Spain and Portugal (Hotz and Brown 2004;WHO 2009). A deficient Zn intake by humans is associated with severe health complications, including impairments of physical growth, immune system and learning ability, combined with increased risk of infections, DNA damage and cancer development (Hotz and Brown 2004;Levenson and Morris 2011). The European Recommended Dietary Intake (RDI) of Zn for humans is 15 mg Zn day -1 (Elmadfa 2009).…”
Section: Introductionmentioning
confidence: 99%